Preliminary results of the implementation of the program to reduce morbidity and prevent mortality from diseases of the circulatory system in workers of locomotive crews - E. A. Zhidkova; E. M. Gutor; V. B. Pankova; M. F. Vilk; I. A. Popova; K. G. Gurevich; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Corporate health programs are a common measure for the primary and secondary prevention of chronic non-communicable diseases.Aim. To study the first implementation results of a Targeted comprehensive program to reduce morbidity and prevent mortality from circulatory system diseases and early cancer detection in employees of JSC "Russian Railways" for the period from 2019 to 2023.Material and methods. The study used a survey of employees of locomotive crews (RLC), which was conducted twice: in the summer of 2018 and February-March 2021. The survey was conducted using a specially designed questionnaire that takes into account the health status of drivers and their assistants, production, and non-production risk factors. In 2018, 10476 questionnaires were collected (>7% of employees), and in 2021 — 14403 questionnaires (>10% of employees). The age structure of railways has not changed, which made it possible to analyze the frequency of occurrence of risk factors in dynamics.Results. In general, the mention of the RLC of the interfering effect of the noise factor, uncomfortable temperature, and undesirable odors in the driver’s cabin decreased for JSC "Russian Railways". The number of smokers on the South-Eastern Railway significantly increased during the study period. The number of people consuming insufficient amounts of vegetables and fruits has increased on the Far Eastern, West Siberian, Krasnoyarsk, and Volga railways. The frequency of workers’ meals at fast food restaurants has increased on the Southeastern Railway. The number of people with a good commitment to the basic principles of a healthy lifestyle has increased on the East Siberian, Trans-Baikal, West Siberian, Kuibyshev, Oktyabrskaya, Sverdlovsk, North Caucasian, and South Ural railways.Conclusion. The conducted research has shown the effectiveness of the initial stage of the implementation of the corporate program to reduce morbidity and prevent mortality from diseases of the circulatory system in RLC. The heterogeneity of the results for different railways was revealed.